KNOWLEDGE OF THE USE OF TRADITIONAL MEDICINE IN DENTAL HEALTH CARE IN JEUMPA VILLAGE, PIDIE ACEH DISTRICT - Teuku Salfiyadi (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Background: Traditional medicine is widely used by the community, this is because traditional medicine is easy to obtain and use, but if it is used and the dosage is not appropriate, it will not be effective in healing. Objective: to determine the relationship between community knowledge and the use of traditional medicine to cure toothache in Pidie District. Methods: This research is analytic in nature with a cross-sectional design. Conducted in Pidie Regency from 10 to 20 February 2022 The research population is all people aged 45-54 years, totaling 88 people. The sample in this study used a random sampling technique, namely a sample of 46 people. The instrument used is a questionnaire sheet by means of interviews. Data analysis used the chi square statistical test. Results: the study showed a lack of knowledge on the use of traditional medicine showed a lack of effort to heal pain, amounting to 26 respondents (65.0%). While good knowledge of the use of traditional medicine shows the achievement of healing toothache by 6 respondents (13%), with a p-value <0.004 from a value of ? = 0.05 because p=0.004 <? = 0.05. The results of statistical tests show that there is a relationship knowledge of the use of traditional medicine with dental health in the community in Pidie District. It can be concluded that there is a significant relationship between knowledge of the use of traditional medicine and healing toothache.